Dry reforming of methane over single-atom Rh/Al2O3 catalysts prepared by exsolution. Issue 7 (15th March 2023) - Mekkering, Martijn J.; Biemolt, Jasper; de Graaf, Jeen; Lin, Yi-An; van Leest, Nicolaas P.; Troglia, Alessandro; Bliem, Roland; de Bruin, Bas; Rothenberg, Gadi; Yan, Ning
Abstract : Single-atom catalysts often show exceptionally high performance per metal loading. Abstract : Single-atom catalysts often show exceptionally high performance per metal loading. However, the isolated atom sites tend to agglomerate during preparation and/or high-temperature reaction. Here we show that in the case of Rh/Al2 O3 this deactivation can be prevented by dissolution/exsolution of metal atoms into/from the support. We design and synthesise a series of single-atom catalysts, characterise them and study the impact of exsolution in the dry reforming of methane at 700–900 °C. The catalysts' performance increases with increasing reaction time, as the rhodium atoms migrate from the subsurface to the surface. Although the oxidation state of rhodium changes from Rh(iii ) to Rh(ii ) or Rh(0) during catalysis, atom migration is the main factor affecting catalyst performance. The implications of these results for preparing real-life catalysts are discussed.